The Skin Microbiota of Eleutherodactylus Frogs: Effects of Host Ecology, Phylogeny, and Local Environment - Garcia-Recinos, Liza; Burrowes, Patricia A.; Dominguez-Bello, Maria (Frontiers in Microbiology, 2019)
Amphibian skin microbiota has a potential protective role against diseases and yet, the effects of environmental and host factors on symbiotic bacterial communities are not well understood. Caribbean frogs in the genus Eleutherodactylus represent a case of congeneric species that differ in ecological specialization by the process of adaptive radiation. We hypothesized that the skin microbiota of Eleutherodactylus frogs would be mostly associated to host ecology, but also differ according to locality, and to a lesser extent to host phylogeny. To test this hypothesis, we swabbed the skin of a total of 98 adult individuals of seven Eleutherodactylus species distributed in two nearby localities in Puerto Rico, Charco Azul (altitude 600 m) and Quebrada (altitude 360 m), and sequenced the V4 region of the 16S rRNA gene. Results showed that locality had a stronger effect on the composition (presence/absence) of skin bacterial communities, than on relative abundance of bacterial taxa. The most ecologically distinct host, E. cooki, and the generalist E. coqui presented, respectively, the most dissimilar and similar microbiota compared to other hosts. Host phylogeny showed a weaker influence on skin microbiota than locality and host species. Results suggest that both local environment and host ecology are structuring the skin bacterial community in these Eleutherodactylus species.